(untitled) (Minerva, 2019)
Millenarism as such did not exist in genuine Etruscan tradition. Only very late texts, influenced by Christian ideas, offer views about thousand years periods, connected with eschatological expectation. Old local tradition was interested in periods of “centuries”, not necessarly of hundred years, which appear sometimes combinated with a cyclical conception of time, including repetition of same events at different periods of time.